Development Of Physical Fitness Testing Instruments In Adult Women Middle-Aged - Diah Ayu Rosalia Tungga Dewi; soni sulistyarto; Noortje Anita Kumaat (UNIVERSITAS NEGERI MAKASSAR, 2023)
physical fitness for the adult women middle-age has various components of physical fitness that cannot be compared to other sports, for this reason it is necessary to develop a series of special physical fitness tests that can measure and develop each component of physical fitness needed by the adult women middle-age. This study uses developmental research. So in this study will develop the types of general physical fitness tests into a series of special physical fitness tests for the adult women middle-age according to their characteristics. In this study, it took about 3 (three) months, from September to December 2022. Data collection in this study was carried out in the morning. The place of this research is in a gymnastic club in Surabaya. In this study using research procedures using research development steps from borg and gall. It was concluded that research on the development of physical fitness test instruments in the adult women middle-age can be used as a reference for further research, and is useful for practitioners conducting tests and measurements on the adult women middle-age.